Cultural Heritage as An Educational Factor in The School Education System (On the example of the Republic of Karakalpakstan) - Bekniyazov Bayrambay Saparbayevich (Genius Journals, 2023)
Karakalpakstan is rich in historical and cultural heritage. The author of the article highlights the problem of familiarizing the schoolchildren to the architectural monuments on the example of the city of Mizdakxana for the purpose of their artistic and aesthetic education. The describe the practice of familiarizing to the monuments of architecture
Keywords: historical complex Mizdakxan; esthetics culture; personality formation